Development of a finer-resolution multi-year emission inventory for open biomass burning in Heilongjiang Province, China - Bin Li; Zehua Xu; Baiyin Liu; Zhimiao Zhang; Wenting Qiu; Wei Wang (Scientific Reports)
Abstract Open biomass burning (OBB) is a significant source of air pollutants, profoundly impacting regional air quality and global climate change. However, due to the lack of high-resolution burned area products, limited biomass data resolution, and inappropriate emission factors (EFs), current OBB emission inventories have significant uncertainties. In this study, we integrated the FireCCI51 burned area product (250 m), high-resolution gridded biomass data, localized EFs, and various statistical survey data to compile a finer-resolution (250 m) and long-term (2001–2020) inventory of 11 pollutants for Heilongjiang Province (an important agricultural and forestry region in China). The results indicated that the annual average OBB emissions in Heilongjiang Province were 12.26, 63.70, 931.60, 17,203.35, 16.09, 171.25, 39.83, 71.22, 184.33, 129.16, and 6.35 Gg for BC, CH4, CO, CO2, NH3, NMVOC, NOx, OC, PM10, PM2.5, and SO2, respectively. Taking PM2.5 as an example, emissions from cropland, forest, and grassland burning accounted for 73%, 26%, and 1% respectively. Geographically, emissions were primarily concentrated in the western, southwestern, and northeastern regions of Heilongjiang. The peak PM2.5 emissions exhibited notable seasonal variation, with maxima occurring in April and October. This is primarily due to the extensive burning of straw during the spring and autumn ploughing seasons. The results of this study provide a detailed multi-year inventory crucial for atmospheric transport models and can support the development of effective pollution control strategies and greenhouse gas mitigation measures.